A qualitative analysis of the interfaces between urban underground metro infrastructure and its environment in London. (August 2021) - Darroch, Nathan; Beecroft, Mark; Nelson, John D.
Highlights: Interfaces between railway-based infrastructure need to be comprehended. Railway asset management requires multi-disciplinary evidence-based data. Multi-disciplinary data gathering assists effective asset management. The AIR processes provide standardised approaches to data collection and sharing. The AIR processes contribute to Building Information Modelling processes. Abstract: As urban environments densify and cities across the world employ urban underground metros for the effective rapid movement of millions of people a day, there is an essential need to ensure the safe continued presence and operation of those metros. To achieve this, the authors argue there is a need for a more detailed qualitative analysis of how urban underground metro infrastructure and its environment interface. Failure to do so could potentially lead to the development of inaccurate asset management data. This would subsequently lead to the implementation of flawed Building Information Modelling processes for 2, 3, and 4D modelling and mapping, of existing and proposed infrastructure. Following a review of existing asset management approaches which confirms the need for qualitative approaches to the analyses of the interfaces, this paper presents findings from a detailed case study, in the Bayswater area of the City of Westminster in West London, UK. The processes employed for the detailed case study form part of proposed (ultimately) standardised approaches to the gathering, analysis, and sharing, of multi-disciplinary evidence-based data, developed by the authors. Such data is essential to enable effective asset and urban management processes, now and for the future.